Введення в культуру in vitro півників низьких (Iris pumila L.) - Twardovska, M.O.; Kunakh, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
Conditions for efficient germination of Iris pumila L. seeds were described. Tissue culture and plants of this species were obtained in vitro. The explants of root origin were found to be able to produce callus on the Murashige and Skoog medium with half content of macro- and micronutrients supplemented with 0.1 mg/L 6-benzylaminopurine and 0.5 mg/L 2, 4-Dichlorophenoxyacetic acid. Conditions for growth of I. pumila plants in greenhouse with a view to their further reintroduction into natural environments were specified.